Pengaruh Derajat Kejenuhan Pada Tanah Gambut Menggunakan Uji Kuat Geser Tanah - Firdaus, Achmad Paksi; Setyanto, Setyanto; Herison, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The soil occupies an important role in the construction of a building, the main benefit of the soil isas a foundation of the construction, there are several soil shear strength tests, such as DirectShear Test, and Vane Shear Test. Each test can produce different test results for the same testobject. This may occur due to different testing procedures and workings of different tools as wellas the main test result targets of each equipment in the determination of soil parameters.Therefore, a careful soil investigation is needed, especially to determine the degree of saturationin peat soils by using soil shear strength test. In this study, the soil tested is a type of peat soiloriginated from the Rawa Seragi area, Belimbing Sari Village, Jabung District, East LampungDistrict.The tests were conducted directly in the laboratory for 12 (twelve) points and at differentdepths with Vane Shear and Direct Shear tools used to calculate the soil and maximum readingability on the torsimeter dial. Based on the test results obtained the average shear strength valueof Vane Shear on saturated soil at 30cm with an average value of 0.0379 and at a depth of 50cmwith an average value of 0.0384 and on unsaturated soil at a depth of 30cm with an average valueof 0.0434 and at a depth of 50cm with an average value of 0.0406 thus obtained a decrease of0.0066.Keywords: Degree of Saturation, Peat Soil, Shear Strength Test